2019
DOI: 10.1002/ange.201811947
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne Versus Ynamide Reactivity: Regioselective Radical Cyclization of Yne‐Ynamides

Abstract: Ynamides are typically more reactive than simple alkynes and olefins. However, a serendipitous observation revealed a rare case where the reactivity of simple alkynes exceeds that of ynamides. This led to the development of a unique sulfur‐radical‐triggered cyclization of yne‐tethered ynamides, which involves attack of the alkyne by a thiyl radical followed by cyclization with the ynamide. A wide range of novel 4‐thioaryl pyrroles that could tolerate common functional moieties and N‐protecting groups were expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…First, the radical precursor undergoes single electron transfer with copper(I) complex (or the photoexcited *Ir III catalyst) to generate a copper(II) species (or Ir IV species) and radical •X (•CF 2 R) which then undergoes intermolecular addition to the alkene part in the ynamide 1 furnishing alkyl radical intermediate I. 17 Intramolecular cyclization to generate vinyl radical intermediate II precedes ipso-cyclization onto the sulfonamide and desulfonylation to generate the N-centered radical intermediate III. Oxidation of III by copper(II) complex (or Ir IV species) would generate the extended cation IV and regenerate the copper(I) catalyst (or Ir III catalyst).…”
Section: T H Imentioning
confidence: 99%
“…First, the radical precursor undergoes single electron transfer with copper(I) complex (or the photoexcited *Ir III catalyst) to generate a copper(II) species (or Ir IV species) and radical •X (•CF 2 R) which then undergoes intermolecular addition to the alkene part in the ynamide 1 furnishing alkyl radical intermediate I. 17 Intramolecular cyclization to generate vinyl radical intermediate II precedes ipso-cyclization onto the sulfonamide and desulfonylation to generate the N-centered radical intermediate III. Oxidation of III by copper(II) complex (or Ir IV species) would generate the extended cation IV and regenerate the copper(I) catalyst (or Ir III catalyst).…”
Section: T H Imentioning
confidence: 99%
“…The use of thiyl radical addition/cyclization has been previously described as a useful route to thiophenes, through clever use of homolytic substitution reactions. Possibly the most recent cyclization of a diyne substrate was reported by Dutta et al, in which a number of pyrroles were prepared ( Scheme 16 ) [ 64 ]. This account describes the use of ynamides and alkynes for cyclization; the authors report a ‘serendipitous observation’ that the reactivity of simple alkynes was found to exceed the traditionally more reactive ynamides moieties for cyclization.…”
Section: Dienes and Diynesmentioning
confidence: 99%
“…Based on the previous findings and our ongoing research on ynamide [26][27][28][29][30] and yne-dienone, [31 -33] we envisioned a gold-catalyzed keteniminium driven dienone-phenol rearrangement of yne-dienone IV, which to the best of our knowledge is rare (Scheme 1,c). The transformation possibly involves dienone-phenol rearrangement with 1,2-migration of 4-substituted ynedienone and a regioselective intramolecular 6-endodig cyclization of in-situ formed aryl-propargyl ether VII cascade (Scheme 1,c).…”
Section: Introductionmentioning
confidence: 99%